Trends and impacts of demographic disparity on JMP ladders for drinking water and sanitation services: further analysis of the Ethiopian demographic and health surveys - Zinabu Assefa Alemu; Ermias Alemayehu Adugna; Badasa Wagari Likasa; Andualem Mekonnen; Tadesse Alemu; Aderajew Mekonnen Girmay (Discover Water, 2023)
Abstract Access to water and sanitation are a major issues for many countries, especially for low- and middle-income nations like Ethiopia. The study aims to identify trends in the use of drinking water and sanitation services using Joint Monitoring Programme (JMP) ladders and to assess the impact of demographic factors on that use. A time trend analysis for water and sanitation services was carried out using JMP ladders using household data from the Ethiopian Demographic and Health Survey (EDHS). Likewise, factors affecting the coverage of water and sanitation service ladders were also determined using a multivariate logistic regression analysis. According to a recent survey, the basic drinking water service trend increased significantly from 18% in 2000 to 57% in 2019 by 217%. In contrast, surface water use declined from 31% in 2000 to 12% in 2019 by 61%. Despite the overall coverage of basic sanitation services grew by 900% (or nine times) from 1% in 2000 to 10% in 2019, the coverage of basic sanitation services decreased by 25% from 8% in 2011 to 6% in 2016. Furthermore, the practice of open defecation decreased by 67% from 81% in 2000 to 27% in 2019. In this study, the availability of drinking water and sanitation services are influenced by many demographic factors. The wealth quantile was used as an example since it has a major impact on the water and sanitation service ladders. Similarly, the age of households’ heads difference significantly affects sanitation but has little effect on water service. The essential trend of water and sanitation services increased significantly. Several factors influencing the progression of water and sanitation service ladders have been discovered. As a result, households should replace the unimproved sanitation facilities with improved sanitation facilities and encourage hand-washing habits to reduce health risks associated with poor sanitation. Furthermore, the effect of demographic factors should be considered in the development of strategies to increase access to drinking water and sanitation services.